Assessment of primary factors causing positive or negative local perceptions on protected areas - Alkan, Hasan; Korkmaz, Mehmet; Tolunay, Ahmet (Journal of Environmental Engineering and Landscape Management, 2009)
The protection of natural resources by strict rules at various legal statuses can generally cause damnification for the local people who are the users of this resource. In case the benefit loss that happens by reason of the prohibitions and limitations that are brought related to the usage of the resource is not corrected and local awareness is not created; negative local perceptions can come out pertinent to this resource and in connection with this, hostile attitudes arise related to the resource that is taken under protection. This case is a significant obstacle in front of being able to provide local participation for resource management. In this study the factors that negatively or positively affected the formation of the perceptions of the local people related to the protected areas are studied with the example of Kovada Lake National Park (KLNP). According to the findings of the study, while 25% of the local people have a positive perception on Kovada Lake National Park, the rest has a negative perception. Statistically significant differences have been found between these two groups whose perceptions show differences in terms of the knowledge levels related to the National Park and some losses of benefit that they had for benefiting from it.Svarbiausių veiksnių, lemiančių atsakomybę dėl veiklos saugomose teritorijose, įvertinimasSantrauka. Dėl griežtų teisėsaugos institucijų taikomų gamtinių išteklių apsaugos taisyklių asmenys, naudojantys šiuos išteklius, gali patirti žalos. Dėl draudimų ir ribojimų prarandama nauda negrįžta, neišugdomas ir sąmoningumas. Pateikiamas kliūties, trukdančios vietiniams žmonėms dalyvauti išteklių valdyme, pavyzdys. Veiksniai, teigiamai ar neigiamai veikiantys vietinių žmonių sąmoningumą dėl saugomos teritorijos formavimo, analizuojami Kovados ežero nacionalinio parko pavyzdžiu. Tyrimų duomenimis, 25 % vietinių gyventojų teigiamai vertino Kovados ežero nacionalinio parko apsaugą, kiti – neigiamai. Statistiškai reikšminiai šių dviejų grupių vertinimo skirtumai buvo rasti pagal suvokimą, grįstą žiniomis apie nacionalinį parką ir praradus naudą.Reikšminiai žodžiai: vietiniai žmonės, vietinis suvokimas, gamtos apsauga, saugomos teritorijos, Kovados ežero nacionalinis parkas, Turkija.Оценка главных факторов, обуславливающих ответственность за деятельность на охраняемых территорияхРезюме. Охрана природных ископаемых на основании строгих правил, диктуемых различными природоохранными учреждениями, может наносить урон лицам, применяющим эти ископаемые. Из-за запретов и ограничений теряется польза от использования ископаемых и в то же время не воспитывается сознательное отношение к охраняемым территориям. В статье представлен пример главных факторов, мешающих местным жителям участвовать в управлении ископаемыми. Факторы, оказывающие положительное или отрицательное воздействие на формирование сознательного отношения местных жителей к охраняемым территориям, анализируются на примере национального парка озера Ковада. На основании данных исследований 25% местных жителей положительно оценивают охрану национального парка озера Ковада, остальные – отрицательно. Статистически значимые различия найдены между этими двумя группами людей, чье представление основано на знаниях о национальном парке и наносимом ущербе.Ключевые слова: местные жители, местное представление, охрана природы, охраняемые территории, национальный парк озера Ковада, Турция.First Published Online: 14 Oct 2010